Projeto de controladores de amortecimento para unidades eólicas de geração baseadas em gerador de indução duplamente alimentado - Zamadei, José Alexandre (2012)
The strong expansion of wind generation is a global trend that changes the structure, planning operation and dynamics of power systems. Thus, it’s important that the units of wind generation take responsibility for the reliability and stability of power system. A good transient performance and good degree of stability for the power system depend of technical studies and of the use of appropriate strategy controls. In this context, this study proposes the inclusion of a additional control loop on generating wind turbines based on doubly fed induction generator. The purpose of the proposed additional control loop is to improve the stability margin to small perturbations of wind turbines and power system. Damping controllers for the proposes additional control loop are designed to damp the oscillations caused by the wind turbines and conventional generating units based on synchronous generator. An analysis to determinate the best control input for the inclusion of the control loop further wind power generation unit is performed using waste transfer function. The analyses and tests are performed using two different test systems: system comprising a single wind unit connected to a infinite bus and a system comprising a wind unit and a wind power generation based on the conventional synchronous generator connected to an infinite bus. Two different methods are adopted for the project / synthesis of the controller of the additional control loop. A project methodology is based on classical control theory and the other is based on modern-robust control theory. The obtained results show that the inclusion of additional control loop was efficient in improving the stability margin of small perturbations of the power system. These results also demonstrate that wind turbines based in doubly fed induction generator can contribute to improving the stability margin of the power system.